Problems with free boundaries for the nonlinear evolution equation in problems of metallurgy, medicine, ecology - Mitropolsky , Yu. A.; Berezovsky, A. A.; Plotnitsky, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider problems with free boundaries for an unknown scalar function and its level surface. We study problems of uniqueness, monotonicity, spatial localization and the existence of solutions. We survey the constructive methods developed for solving specific problems and mathematical prediction in the corresponding areas of the natural sciences.